Study of the Development Cycle of Cotton Bollworm Helicoverpa Armigera - Mavlonjonovich, Rahimov Mansurbek (American Journal of Biology and Natural Sciences, 2025)
The cotton bollworm Helicoverpa armigera (Hübner) is a widespread genus of Lepidoptera insects found on various crops throughout the world. This type of insect causes great economic damage as an agricultural pest. During the researches, the morphological characteristics of eggs, larvae, cocoons and imagos were studied during the development cycle of the cotton bollworm.